ATTACHWELL: A CONCEPTUAL MODEL INTEGRATING ATTACHMENT-BASED WELLNESS IN PUBLIC HEALTH THROUGH A SYSTEMATIC LITERATURE REVIEW - Tony Michael (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2026)
Background: Attachment theory provides a framework for understanding relational influences on wellness. This manuscript examines its application across public health initiatives, integrating attachment principles with SAMHSA's eight wellness domains. Purpose: The objectives are to demonstrate how secure attachment supports well-being across domains and introduce the AttachWell Model for applying attachment-informed strategies within public health. Method: A conceptual synthesis of 78 peer-reviewed studies published between 2000 and 2024 was conducted. Studies were selected based on relevance to attachment and wellness outcomes, and quality was assessed using the MMAT. Results: Evidence is strongest for emotional, intellectual, and social wellness domains, with preliminary support for physical and spiritual domains. Evidence is limited to occupational, financial, and environmental domains, highlighting research gaps. The synthesis shows secure attachment promotes resilience, emotion regulation, and social connectedness. Conclusion: The AttachWell Model advances theory by positioning secure attachment as a structural determinant of wellness. Implementation pathways include interventions, policy initiatives, and evaluation strategies. The model provides a framework for integrating attachment-informed strategies into public health practice, though further empirical validation is required. Abstrak Latar Belakang: Teori keterikatan menyediakan kerangka untuk memahami pengaruh relasional pada kesejahteraan individu dan komunitas. Naskah ini mengkaji penerapannya dalam inisiatif kesehatan masyarakat, mengintegrasikan prinsip keterikatan dengan domain kesejahteraan SAMHSA. Tujuan: Menunjukkan bagaimana keterikatan aman mendukung kesejahteraan dan memperkenalkan Model AttachWell untuk menerapkan strategi berbasis keterikatan dalam kesehatan masyarakat. Metode: Sintesis konseptual dari 78 studi peer-review dilakukan. Studi dipilih berdasarkan relevansi dengan hasil keterikatan dan kesejahteraan, dinilai menggunakan MMAT. Hasil: Bukti terkuat untuk domain kesejahteraan emosional, intelektual, dan sosial, dengan dukungan awal untuk domain fisik dan spiritual. Bukti terbatas untuk domain pekerjaan, keuangan, dan lingkungan. Sintesis menunjukkan keterikatan aman mempromosikan ketahanan, regulasi emosi, dan keterhubungan sosial. Kesimpulan: Model AttachWell memajukan teori dengan memposisikan keterikatan aman sebagai penentu kesejahteraan holistik. Jalur implementasinya mencakup intervensi, kebijakan, dan strategi evaluasi. Model ini menyediakan kerangka berbasis bukti untuk mengintegrasikan strategi keterikatan ke dalam praktik kesehatan masyarakat.